Our ally China : the story of a great people and its man of destiny - Chiang Kai-Shek - Owen, Frank (London : W.H. Allen & Co., 1942)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Chiang Kai-shek.; politieke geschiedenis; Wereldoorlog 2; China